Enhanced hydrogen production performance at intermediate temperatures through the synergistic effects of binary oxygen carriers. (15th October 2019) - Qiu, Yu; Zhang, Shuai; Cui, Dongxu; Li, Min; Zeng, Jimin; Zeng, Dewang; Xiao, Rui
Highlights: Co dopant improves Fe reduction. CoFeOy exhibits reversible phase change. High redox performance is obtained at intermediate temperatures. Abstract: Operating oxygen carrying materials under a relatively low temperature has been the most important goal for the scalable application of chemical looping hydrogen production, so as to increase the durability and process economy. However, low temperatures have a degrading effect on the kinetics of the redox reactions, when it comes to the hydrogen production, leading to decreased oxygen storage capacity and thereby the low hydrogen yield and production rate. Although improved performance at intermediate temperatures can be found in materials composed of rare earth oxides, the high cost hindered the industrial application of these materials. In this paper, we prepared a series of binary oxygen carrier materials (CoFeOy, NiFeOy, CuFeOy ) and investigated the chemical looping hydrogen production performance at intermediate temperatures. CoFeOy exhibited the highest hydrogen yield (∼11.17 mmol g −1 ) and peak hydrogen production rate (∼0.23 mmol g −1  s −1 ) at 650 °C. To explore the synergistic effects causing the improved performance, XPS and TPR study was carried out. The results exhibited that the full reduction of Fe3 O4 to FeO can be found at ∼800 °C for CoFeOy, whist Co dopant was highly reducible with reversible phase change in the whole redox period at the intermediate temperature. The redox chemistry obtained in this work can be helpful for the design of the oxygen carrier materials for low temperature chemical looping applications.